Nitrate Remediation: The Importance of the Advanced Nitrogen Cycle in Remedy Selection. Issue 1 (17th December 2015) - Vance, David; Neary, Leigh; Sueker, Julie; Nelson, Denice
Abstract : Nitrate has become an increased regulatory concern due to gradual deterioration of surface and groundwater quality primarily related to widespread fertilizer use. Remediation of nitrate is a relatively straightforward process; however, nitrate impacts to groundwater are often a symptom of a sustained source from another nitrogen form (e.g., ammonia, ammonium nitrate, urea), analogous to how nonaqueous phase liquid can serve as a long‐term source of volatile organic compounds in groundwater. Understanding the various nitrogen transformation reactions when selecting, implementing, or documenting a remedy associated with nitrate is therefore critical to successfully reaching remedial endpoints. Case studies are presented that highlight in situ remedial successes with nitrogen‐impacted groundwater and discuss the key considerations that should be factored into remedy application. ©2015 Wiley Periodicals, Inc.